The New Informational Paradigm: Developing Practice-Led Approaches to the Use of Mobile ICT in Social Work. (10th November 2017) - Baker, Steven; Warburton, Jeni; Hodgkin, Suzanne; Pascal, Jan
Abstract: Information and Communication Technology (ICT) has profound impacts on society as people integrate technology into their lives. Social work is similarly influenced by ICT as workplaces, individual practitioners and clients adopt new forms of technology and this has prompted an increasing focus on the implications of technology on all aspects of professional practice. Drawing on the work of Spanish sociologist Manuel Castells as its theoretical foundation, this article reports on a Participatory Action Research (PAR) project that sought to understand the potential practice-led integration of ICTs with traditional social work practice at an organisation in rural Victoria, Australia. Eight participants were provided with tablet computers and collaborated with the researcher over a period of eight months to trial ways in which ICTs might complement traditional face-to-face practice in the field. Findings highlight a range of benefits and challenges in adopting a practice-led approach that spanned three key themes: successful practice-led approaches, technological friction and challenges inherent in what Castells describes as the transition to network enterprises . Findings highlight the need for ongoing research and engagement to ensure that technological advances are implemented in ways that are consistent with the enduring ethics and philosophies of the social work profession.